EFFICACY AND TOLERABILITY OF LACOSAMIDE (VIMPAT) FOR TREATMENT OF EPILEPSY IN ADULTS (A REVIEW) - O. A. Pylaeva; K. Yu. Mukhin; M. B. Mironov (Русский журнал детской неврологии)
In spite of the significant progress achieved in epileptology, resistant forms of epilepsy comprise about 30 % of all cases of epilepsy. The articles reviews modern concepts and basic mechanisms of pharmacoresistance, as well as the ways to overcome them. The authors presented a detailed review of modern literature devoted to studies of efficacy, safety, and tolerability of the new antiepileptic drug (AED) lacosamide (Vimpat®) with uncontrolled epilepsy. Lacosamidе is registered in Russia for additional therapy of patients of 16 y.o. and older with focal seizures with or without secondary generalization. The drug is a functionalized amino acid. The assumed action mechanism differs from that of other AEDs: this drug selectively lowers the pathological hyperactivity of neurons without affecting their physiological activity, decreases abnormal epileptogenic neuronal excitability, selectively enhances slow inactivation of sodium channels without affecting rapid inactivation. Lacosamidе has the following pharmacokinetic advantages: linear kinetics; the drug is a weak inducer of liver enzymes (CYP) and, therefore, does not alter the metabolism of other AEDs and is only slightly bound to plasma proteins (< 15 %). Clinical studies have shown the efficacy and good tolerability of lacosamidе by patients with focal seizures; the dosage of the drug of 400 mg/day was assessedto be optimal. Efficacy and good tolerability of lacosamidе has been confirmed by postmarketing studies after beginning of its broad use in clinical practice. Frequent side effects associated with the therapy ( 15 %) include dizziness, headache, drowsiness, nausea, and diplopia. Concurrent intake of other AEDs that block sodium channels statistically significantly increased the risk of arising of side effects associated with the therapy. Pharmacoeconomic analysis of several studies showed favorable indicator of lacosamidе regarding the cost/efficacy criterion for treatment of focal epileptic seizures resistant to therapy.